2017
DOI: 10.1105/tpc.16.00825
|View full text |Cite
|
Sign up to set email alerts
|

Polar Localization of the NIP5;1 Boric Acid Channel Is Maintained by Endocytosis and Facilitates Boron Transport in Arabidopsis Roots

Abstract: Boron uptake in is mediated by nodulin 26-like intrinsic protein 5;1 (NIP5;1), a boric acid channel that is located preferentially on the soil side of the plasma membrane in root cells. However, the mechanism underlying this polar localization is poorly understood. Here, we show that the polar localization of NIP5;1 in epidermal and endodermal root cells is mediated by the phosphorylation of Thr residues in the conserved TPG (ThrProGly) repeat in the N-terminal region of NIP5;1. Although substitutions of Ala f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 80 publications
4
74
0
Order By: Relevance
“…Xylem B concentrations were significantly lower in the overexpressors demonstrating that the shoot‐driven B translocation is hampered in the overexpressers which is the limiting element for adequate delivery of sufficient B to low‐transpiring tissues like the young and developing leaves as well as the meristem (Figure ). In respect to B translocation from the soil to the shoot it was shown that both the AtNIP5;1 boric acid channel as well as the active xylem loading transporter AtBOR1 have to be localized polarly in specific root cell types to maintain the important directional nutrient transport of B (Takano, Miwa, Yuan, von Wirén, & Fujiwara, ; Wang et al., ). Recently it was speculated, that improper localization of AtNIP5;1 at the stele side of the cells can impair the B gradient from the cytosol to the apoplast generated by AtBOR1 (Yoshinari & Takano, ).…”
Section: Discussionmentioning
confidence: 99%
“…Xylem B concentrations were significantly lower in the overexpressors demonstrating that the shoot‐driven B translocation is hampered in the overexpressers which is the limiting element for adequate delivery of sufficient B to low‐transpiring tissues like the young and developing leaves as well as the meristem (Figure ). In respect to B translocation from the soil to the shoot it was shown that both the AtNIP5;1 boric acid channel as well as the active xylem loading transporter AtBOR1 have to be localized polarly in specific root cell types to maintain the important directional nutrient transport of B (Takano, Miwa, Yuan, von Wirén, & Fujiwara, ; Wang et al., ). Recently it was speculated, that improper localization of AtNIP5;1 at the stele side of the cells can impair the B gradient from the cytosol to the apoplast generated by AtBOR1 (Yoshinari & Takano, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Casparian strips at the exodermis and endodermis, where OsLsi1 and OsLsi2 are located, are also important for efficient uptake, probably by preventing the backflow of Si from the aerenchyma or the stele. The mechanisms responsible for the control of polarity of these transporters are poorly understood, but a recent study has shown that the polar localization of a B channel AtNIP5;1 in epidermal and endodermal root cells is maintained by clathrin-mediated endocytosis, which is dependent on the phosphorylation of Thr residues in the conserved ThrProGly (threonine-proline-glycine, TPG) repeat in the N-terminal region of AtNIP5;1 in Arabidopsis (Wang et al, 2017). The Thr to alanine (Ala) substitution did not affect the B transport activity of green fluorescent protein (GFP)-AtNIP5;1 in Xenopus laevis oocytes, but did inhibit the ability to complement B translocation to shoots and to rescue growth defects in nip5;1-1 mutant plants under B-limited conditions.…”
Section: Polarity Of Transporters For Mineral Elementsmentioning
confidence: 99%
“…The internalized receptor complexes are either recycled back to the cell surface or routed to the vacuole for degradation and signaling termination. Recent studies revealed that the molecular mechanisms behind RME are highly conserved, in all eukaryotes, including plants, pointing out major roles for clathrin and post-translational modifications (PTMs) of PM receptors, such as ubiquitination and phosphorylation (Nimchuk et al 2011;Ben Khaled et al 2015;Martins et al 2015;Mbengue et al 2016;Ortiz-Morea et al 2016;Erwig et al 2017;Wang et al 2017;Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 99%